Integrated CO2 Storage and Brine Extraction. (July 2017) - Hunter, Kelsey; Bielicki, Jeffrey M.; Middleton, Richard; Stauffer, Philip; Pawar, Rajesh; Harp, Dylan; Martinez, Daniella
Abstract: Carbon dioxide (CO2 ) capture, utilization, and storage (CCUS) can reduce CO2 emissions from fossil fuel power plants by injecting CO2 into deep saline aquifers for storage. CCUS typically increases reservoir pressure which increases costs, because less CO2 can be injected, and risks such as induced seismicity. Extracting brine with enhanced water recovery (EWR) from the CO2 storage reservoir can manage and reduce pressure in the formation, decrease the risks linked to reservoir overpressure (e.g., induced seismicity), increase CO2 storage capacity, and enable CO2 plume management. We modeled scenarios of CO2 injection with EWR into the Rock Springs Uplift (RSU) formation in southwest Wyoming. The Finite Element Heat and Mass Transfer Code (FEHM) was used to model CO2 injection with brine extraction and the corresponding increase in pressure within the RSU. The model was analyzed for pressure management, CO2 storage, CO2 saturation, and brine extraction due to the quantity and location of brine extraction wells. The model limited CO2 injection to a constant pressure increase of two MPa at the injection well with and without extracting brine at hydrostatic pressure. We found that brine extraction can be used as a technical and cost-effective pressure management strategy to limit reservoir pressure buildup and increase CO2 storage associated with a single injection well.